New records of five Staurothele species (Verrucariacaea, Ascomycota) from Iran - Abkouh, Abdul Saleh Kamyabi; Iranbakhsh, Alireza; Moniri, Mahroo Haji; Asri, Younes (Acta Biologica Szegediensis, 2022)
This study aimed to the taxonomic investigation of the genus Staurothele (Ascomycota, Verrucariaceae) in northeast Iran. Lichen samples were collected from the Khorasan Razavi province and their morphological, anatomical, and ecological features were studied. Five species (Staurothele lecideoides, Staurothele frustulenta, Staurothele drummondii, Staurothele rufa, and Staurothele polygonia) were documented for the first time from Iran.